(untitled) (Baghdad Science Journal, 2009)
This study was carried out to assess genetic diversity of ten cultivars of Rice (Oryza sativa L.). One of DNA markers based on Polymerase Chain Reaction (PCR) was used namely DAF markers (DNA Amplification Fingerprint). Six primers were tested, the results showed, that no amplification products using the primers OPD.14 and OPM.5. Two primers (OPX.8 and OPT.2) produced monomorphic band across all cultivars, while only two primers generated polymorphic bands. The number of total bands produced from one of them (OPN.7) were sixteen. Also this primer produced ten polymorphic profiles (DAF patterns) which were unique to the ten cultivars that could be distinguished. The number of total bands generated by primer OPX.1 were thirteen and this primer produced eight polymorphic patterns which was unique for distinguishing six cultivars. This means that DAF markers were able to identify all rice cultivars using only two primers reflecting the high potentialities of these markers for their applications in fingerprinting.